The Rhetoric of Argumentation in Al-Hamadhani`s Harzi Maqāmāh - Al-Shalabi, Nahla (Dirasat: Human and Social Sciences, 2024)
Objectives: This study explores the mechanics of argumentation in the Harzi Maqāmāh through investigating the intrinsic content that represents its deep structure and underpins the author’s artistic craft of generating meaning out of structure. Because verbal structure is governed by the rationale of its genesis, the foregrounding of its corresponding intended purport becomes the main function of the Maqāmāh, including its rhetorical mysteries which contribute to producing a persuasive impact on the text’s receiver. Consequently, more light is shed on the situations in which such persuasive impact takes place. Methods: The study uses sample extracts from the Maqāmāh to orient argumentative significance through various stylistic options. This was done through an analytical study of the rhetorical linguistic levels (expression, eloquence, and meaning) that Badi' al-Zaman Al-Hamadhani employed. The study then represented these aspects using the ladder of persuasion, which reflected the extent of Al-Hamadhani's creativity and persuasive abilities. Data analysis depended on the availability of textual evidence. Results: The Maqāmāh proved to be rich in rhetorical devices that allowed the text to possess the power of persuasive literary enjoyment, conveying a social message that called for combating the wretched submission to superstition and witchcraft, and exposed the foolishness of its victims. These rhetorical devices manifested through al-Hamdhani's use of various arguments, relying on verbal actions, particularly the most effective ones (genuine interrogation) and figures of speech (metonymy and declaration). Their aesthetic power transformed into a source of persuasion. The author's utilization of persuasive techniques (conciseness, emphasis, and denial) became a prominent characteristic in the structure of the Maqāmāh. Conclusion: The study contends that robust argumentative mechanics are manifest in the style of Badi’e Al-Zaman Al-Hamadhani. The tools he deployed include rhetorical flourish, appealing prosodic traits, and superb stylistic features embedded in diverse semantic content and rhythmical patterns.